DOES FIRM SIZE HAVE A MODERATING EFFECT ON FINANCIAL DISTRESS? EVIDENCE: INFRASTRUCTURE SECTOR LISTED IN INDONESIA STOCK EXCHANGE - Andaris, Ibnu; Sunita Dasman (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2024)
This study aims to gather more systematic and complete information about factors that affect financial distress. This study's testing is based on secondary data, with a purposive sample of 41 samples collected overall. With the use of the eviews 12 software package, the data analysis in this study employs logistic regression and moderated regression analysis. The study's findings demonstrate the importance of leverage and liquidity, but not the importance of profitability or firm size. However, the business size has no effect on the profitability variable; only the liquidity and leverage variables are affected. The variables related to liquidity and leverage yielded the most significant findings.